The ROLE OF LEVEL OF INCOME AND EDUCATION ON DIGITAL DIVIDE: A LOOK AT JAKARTA WORK FORCE - Heddry Purba; Francis Hutabarat (Program Studi Magister Manajemen Universitas Advent Indonesia, 2022)
Communication technologies is important in supporting economic, human, and social growth. However, it common knowledge that communication technologies are differ between countries. And the digital difference inside nations can be as high as that between countries. ). The objectives of this study are to assess the Indonesia home digital divide for its Jakarta workforce and to examine the demographic features, specifically: education and level of income as factors influencing digital divide. The study is descriptive and survey questionnaire is employed. Indonesian workers in Jakarta and graduates of the Indonesia Adventist University in Bandung are the study's subjects. There are 239 sample of the study. Frequencies, correlation, significant test, and regression test were used in the analysis. The study found that, simultenously, there is a significant relationship between education and level of income on digital divide of Jakarta workforce. The study also indicates there is no significant relationship based on t-test between education and digital divide. On the other hand, level of income shows that it has significant result with t-test at 10% level of significant.